The gas accessible membrane electrode (GAME): a versatile platform for elucidating electrocatalytic processes using real time and in situ hyphenated electrochemical techniques - Zhang,G; Kucernak,ARJ (ACS Catalysis, 2020)
A gas accessible membrane electrode (GAME) is presented as a versatile tool for electrocatalysis research. With the use of an ultrathin and flat 12 μm thick porous electrode complimented by an efficient gas-circulating loop, the GAME facilitates rapid mass transport of reactants and products at the three-phase interface, enabling electrocatalytic processes to be investigated with fine kinetic details at high current densities (A cm–2) using only μg cm–2 of catalyst. The mass transport rate constant of the GAME is generally 1–2 orders of magnitude higher than those achieved using conventional techniques. The gas handling protocol ensures better utilization and fast switching of different gaseous environments within a few seconds, thereby reducing the use of gases and allowing for measurement of transient responses. This electrochemical configuration can be further coupled with a range of other analytical approaches, such as micro-/nanoelectrodes, mass spectrometry, photocatalysis, and Fourier-transform infrared spectroscopy for real-time/in situ electrochemical measurements, where reaction intermediates and products can be readily characterized. These innovative types of hyphenated platforms can be applied to study complex gas-to-fuel conversion processes (e.g., carbon dioxide electroreduction), in which multiple species need to be simultaneously identified and quantified to illustrate the dynamic product distribution. Moreover, the configuration can be possibly adapted for operando synchrotron-based X-ray characterization.